Accentedness Perception in L2: An Investigation of Thai Monophthong Pronunciation of Chinese Students - Peng Hou; Sarawut Kraisame (Languages)
This paper aims to investigate the Thai monophthong pronunciation of Chinese students speaking Thai as a second language (L2), and to examine how native Thai listeners perceived these Chinese-accented Thai monophthongs. This study involves an acoustic analysis targeted on the Thai monophthongs articulated by Chinese students of Thai (n = 15) in a picture description task in terms of duration and quality. The participants exhibited varying proficiency levels in different monophthongs, with the greatest difficulty being with Thai back monophthongs and certain central monophthongs, including /ɔ, ɔː/, /o, oː/, and /ɤː/. Moreover, a perception experiment among 30 native Thai listeners proved that Chinese students’ pronunciation of Thai monophthongs had varying levels of impact on accentedness perception. Specifically, /ɯ/, /ɤ/, /o/, /ɔ/, and their long counterparts significantly influenced accentedness perception. Conversely, /i/, /e/, /ɛ/, /a/, /u/, and their long counterparts showed less robustness in predicting the level of accentedness. Among the whole Thai monophthong inventory, teachers should prioritize those monophthongs that significantly influence accentedness perception for teaching Thai pronunciation to Chinese students.